Unexpected organic hydrate luminogens in the solid state - Feng Zhou (Nature Portfolio, 2021)
Developing organic photoluminescent materials with high emission efficiencies in the solid state under a water atmosphere is important for practical applications. Here, the authors report the formation of intra- and intermolecular hydrogen bonds in a tautomerizable Schiff base and intercalation of water in the crystal lattice leading to a luminescent organic hydrate.